Candida leandrae sp nov., an asexual ascomycetous yeast species isolated from tropical plants - Ruivo, CCC; Lachance, M. A.; Bacci, M.; Carreiro, S. C.; Rosa, C. A.; Pagnocca, F. C. (Soc General Microbiology, 2004)
The novel yeast species Candida leandrae is described based on eight isolates from decaying fruits of Leandra reversa Cogn. (Melastomataceae) in an Atlantic rainforest site in Brazil, one from a Convolvulaceae flower in Costa Rica and one from a drosophilid in Hawai'i. The strains differed in their colony morphology, one being butyrous and smooth and the other being filamentous and rugose. Sequences of the D1/D2 domains of the large-subunit rRNA gene from both morphotypes were identical. C. leandrae belongs to the Kodamaea clade and is closely related to Candida restingae. The two species can be separated on the basis of growth at 37degreesC and the assimilation of melezitose, negative in the novel species. The type culture of C. leandrae is strain UNESP 00-64R(T) (= CBS 9735(T) = NRRL Y-27757(T)).